An Exploration of Teachers’ Pedagogical Knowledge on Teaching Practical Skills in Fashion and Fabrics to High School Learners - Mpofu, Molyn; Magagula, Hlengiwe; Manwa, Lokadhia; Manwa, Lilian (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
Fashion and Fabrics is a discipline that involves practical and theoretical skills, and to achieve better results, teachers need to possess pedagogical knowledge for teaching practicals as well. This study aimed to establish the teachers' pedagogical knowledge for teaching Fashion and Fabrics practical skills in Eswatini High Schools. This qualitative study utilized a descriptive research design to get in-depth information. A sample of 16 Fashion and fabric teachers was purposively selected, with eight being interviewed, while the others were observed during their practical lessons. Data were analyzed using thematic analysis. The study results show that Fashion and Fabrics teachers need to gain pedagogical knowledge in teaching Fashion and Fabrics practical skills. They must prepare for valuable lessons, as evidenced by a need for proper student-sitting arrangements. Teachers were found not to use visual aids and supervise students' work for corrective feedback when necessary. The study concludes that Fashion and fabric teachers need to be stronger in content knowledge and pedagogical competencies, essential for effective learning; hence, students' achievements could have been higher. The study recommends that the training institutions stress peer teaching of Fashion and Fabrics practicals for more practice.